Grid Tied Photovoltaic System with Perturb and Observe Maximum Power Point Controller and LCL Filter - Pilla, Ramana; Hareesh Kumar, Jallu; Chandana, Adavipalli (International Journal of Engineering and Technology, 2018)
This paper describes a grid tied photovoltaic (PV) system along with maximum power point tracking (MPPT) and LCL filter. A PV model is developed using mathematical equations of solar cell. This PV module is controlled and optimized with MPPT algorithm. The maximum power point (MPP) tracking is implemented using Perturb and Observe (P&O) algorithm from the solar array and given to DC-DC boost converter. The enhancement of unfettered PV Voltage is achieved using boost converter and also used to verify the precision of MPPT technique. Using inverter controller, the boost converter DC output voltage is converted into AC voltage. The phase and frequency of the grid is tracked using phase locked loop (PLL) to integrate the inverter with the grid. In addition to this, to diminish the harmonics in the inverter output an LCL filter is used. The performance of grid tied photovoltaic system is extensively simulated with MATLAB software.